Gorszyciel, deprawator, demoralizator – o nazwach osób nieprzestrzegających norm - Lisczyk, Karolina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The aim of the article is to make an attempt at answering the question: what kinds of attitudes and actions make someone described as gorszyciel [offender], deprawator [depraver] or demoralizator [demoraliser]. The research material was obtained from four electronic corpuses of contemporary Polish. Qualitative and quantitative analysis of the contexts of the use of these nouns, preceded by a review of data from dictionaries, showed that despite their similarity, each of them is associated with specific issues more often than the others. However, all of them refer to breaking not only moral, but also legal and religious standards. Sentences with feminine forms of those nouns illustrate the asymmetry in the way women and men are described and are limited to violating moral rules.